Ideologies of choice : a theoretical analysis of player agency in video games : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Creative Enterprise at Massey University, Wellington, New Zealand - Hoare, James (Massey University, 2021)
Player interaction is a definitive feature of video games, and the choices that are made when playing games create personalised individual experiences for each player. When there are tangible responses to their actions, players decisions within game worlds lead to an experience of agency. This exegesis explores a theoretical analysis of both video games and literature to suggest a different perspective on player agency; that player choices function as a response to the constructed ideologies of video game worlds and are shaped by the player’s relationship with their character. The goal of this analysis is to understand whether non-consequential choices enhance a player’s experience of a linear game narrative. This exegesis accompanies my work within Project: Mystic, a linear mystery game set in 1920’s Aotearoa. Linear video games have predetermined narratives so to aide in the development of Project: Mystic this exegesis explores player agency through the relationship between the player and the player character and the designed ideology of the game world. On the relationship between the player and the player character, this exegesis explores ideas of differing player and player character knowledge, the designation of “I” on the player character, and autonomy and desire in restrictive game worlds. On video game worlds I explore necessary and voluntary player actions, the effect of a player’s participation in a game narrative, and the role of player autonomy within the constructed ideology of a game world. Through a theoretical analysis of video game literature and the application of established theoretical texts on agency as a perspective to explore player agency in video games, this exegesis proposes an analysis on player agency in linear video games that was utilised in the development of puzzles and game mechanics for Project: Mystic. This exegesis also outlines the development of Project: Mystic and how this research informed its production.
Keywords: 330310 Interaction and experience design